An ecological investigation on weeds of paddy field at Pokhara, Nepal - Thapa, Chandra Bahadur; Jha, Pramod Kumar (Journal of Natural History Museum, 2008)
The present investigation, conducted during the rainy seasons of 1996-1997 revealed 76 wood species infesting the paddy field. The general survey of experimental paddy field for taking observations, indicates that the dominant families include Poaceae, Cyperaceae, Asteraceae, Commelinaceae and Lythraceae. Dicot families (16) were greater in number as compared to monocot families (6) and in respect to this fact 40 and 34 species of weeds belong to monocots and dicots respectively. The percentage occurrence of the weeds and the rice plant, based on total population of the area 50cm2 were found to be 90.4 and 9.6 respectively and weed density 222 m-2 Poaceae (17 spp.) and Cyperaceae (15 spp.) were the dominant families. On the basis of important value index (IVI), the major dominating weed species were: Ageratum conyzoides, Cynodon dactylon, Ischaemum rugosum, Echinochloa crus-galli and Cyperus rotundus. Besides, two species of pteriodphytes (Ceratopteris thalictroides and Marsilea minuta) and an insectivorous plants Utricularia exolata were also recorded. J. Nat. Hist. Mus. Vol.22, 2005 p.71-78